OPTIMALISASI PERDAGANGAN LINTAS BATAS DAN KAWASAN EKONOMI KHUSUS SEBAGAI STRATEGI KERJA SAMA EKONOMI INDONESIA–MALAYSIA - Melyana R Pugu (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study examines the optimization of cross-border trade and Special Economic Zones as strategic instruments for strengthening Indonesia–Malaysia economic cooperation in border areas. Border regions between Indonesia and Malaysia have long served as dynamic economic spaces shaped by proximity, social interaction, cultural ties, and daily trade. However, cross-border trade has not yet fully contributed to local economic transformation due to infrastructure limitations, regulatory differences, informal trade practices, weak logistics systems, and limited capacity of local business actors. Using a library research method with a descriptive-qualitative approach, this study analyzes academic literature, policy documents, official reports, and recent studies related to cross-border trade, Special Economic Zones, and bilateral economic cooperation. The findings indicate that cross-border trade serves as an economic foundation for border communities, while Special Economic Zones can provide added value through investment, industrial processing, logistics development, export facilitation, and employment creation. The integration of these two instruments can transform border areas from peripheral zones into productive and competitive cross-border economic corridors. Furthermore, the study highlights the importance of regulatory harmonization, infrastructure connectivity, institutional coordination, digital trade systems, and empowerment of local communities and SMEs. The renewal of the Indonesia–Malaysia Border Trade Agreement provides an important legal foundation, but its effectiveness depends on practical implementation and multi-stakeholder collaboration. This study concludes that optimizing cross-border trade and Special Economic Zones can strengthen bilateral economic cooperation, enhance local economic resilience, reduce dependency, and support ASEAN regional economic integration.